Comparative Effectiveness of Sphincter-Sparing Surgery Versus Abdominoperineal Resection in Rectal Cancer. Issue 1 (January 2015) - Russell, Marcia M.; Ganz, Patricia A.; Lopa, Samia; Yothers, Greg; Ko, Clifford Y.; Arora, Amit; Atkins, James N.; Bahary, Nathan; Soori, Gamini S.; Robertson, John M.; Eakle, Janice; Marchello, Benjamin T.; et al.
<x xml:space="preserve">Abstract</x> Objective: National Surgical Adjuvant Breast and Bowel Project (NSABP) R-04 was a randomized controlled trial of neoadjuvant chemoradiotherapy in patients with resectable stage II-III rectal cancer. We hypothesized that patients who underwent abdominoperineal resection (APR) would have a poorer quality of life than those who underwent sphincter-sparing surgery (SSS). Methods: To obtain patient-reported outcomes (PROs) we administered two symptom scales at baseline and 1 year postoperatively: the Functional Assessment of Cancer Therapy-Colorectal (FACT-C) and the European Organization for the Research and Treatment of Cancer module for patients with Colorectal Cancer Quality of Life Questionnaire (EORTC QLQ-CR38). Scoring was stratified by nonrandomly assigned definitive surgery (APR vs SSS). Analyses controlled for baseline scores and stratification factors: age, sex, stage, intended surgery, and randomly assigned chemoradiotherapy. Results: Of 1, 608 randomly assigned patients, 987 had data for planned analyses; 62% underwent SSS; 38% underwent APR. FACT-C total and subscale scores were not statistically different by surgery at 1 year. For the EORTC QLQ-CR38 functional scales, APR patients reported worse body image (70.3 vs 77.0, P = 0.0005) at 1 year than did SSS patients. Males undergoing APR reported worse sexual enjoyment (43.7 vs 54.7, P = 0.02) at 1 year than did those undergoing SSS. For the EORTC QLQ-CR38 symptom scale scores, APR patients reported worse micturition symptoms than the SSS group at 1 year (26.9 vs 21.5, P = 0.03). SSS patients reported worse gastrointestinal tract symptoms than did the APR patients (18.9 vs 15.2, P < 0.0001), as well as weight loss (10.1 vs 6.0, P = 0.002). Conclusions: Symptoms and functional problems were detected at 1 year by EORTC QLQ-CR38, reflecting different symptom profiles in patients who underwent APR than those who underwent SSS. Information from these PROs may be useful in counseling patients anticipating surgery for rectal cancer.